Compressive strength evaluation of coral aggregate seawater concrete (CAC) by non-destructive techniques. (1st December 2018) - Tan, Yongshan; Yu, Hongfa; Mi, Renjie; Zhang, Yan
Highlights: Non-destructive testing was carried out on coral aggregate seawater concrete (CAC). Rebound hammer, ultrasonic pulse velocity and combined method were employed. Various mathematical models of strength prediction of CAC by various methods have been achieved. The applicability of testing strength curves of OPC and LAC to CAC were also discussed. Abstract: Coral aggregate concrete (CAC) is a material that is becoming increasingly popular in reef concrete structural applications. In the present work, CAC was cast in a wide range of compressive strength varying from 30 to 75 MPa. The ultrasonic pulse velocity (UPV), the rebound hammer (RH) and the compressive strength ( fcu ) test were conducted at 28 and 90 days. The influence of sisal and age on the relationship between fcu - UPV and fcu - RH were discussed. Additionally, the mathematical model of strength prediction by UPV, RH and the combined method were established (testing strength curve, TSC). Finally, the applicability of TSC of Portland concrete (OPC) and lightweight aggregate concrete (LAC) to CAC were also discussed. The results show that the curing ages have a certain influence on the TSC. Therefore, the 28 d and 90 d strength test curves for special engineering by UPV, RH and combined methods were established. For ease of use, the TSC for regional engineering by various methods were also established. The relative standard error ( er ) of the TSC can meet the requirements of the specification for special and regional. In addition, the TSC of OPC and LAC does not apply to the strength prediction of CAC through the error analysis.